Combined genetic-pharmacologic inactivation of tightly linked ADAMTS proteases in temporally specific windows uncovers distinct roles for versican proteolysis and glypican-6 in cardiac development - Mead, Timothy J.; Bhutada, Sumit; Foulcer, Simon J.; Peruzzi, Niccolò; Nelson, Courtney M.; Seifert, Deborah E.; Larkin, Jonathan; Tran-Lundmark, Karin; Filmus, Jorge; Apte, Suneel S. (Matrix biology, 2024)
• Combined genetic-pharmacologic ADAMTS1 and ADAMTS5 inactivation in mice.• Degradomics identification of putative ADAMTS1 and ADAMTS5 substrates.• A requirement for versican proteolysis and glypican-6 in heart development.• Novel roles for ADAMTS1, ADAMTS5 and glypican-6 in hedgehog signaling in the heart. Extracellular matrix remodeling mechanisms are understudied in cardiac development and congenital heart defects. We show that matrix-degrading metalloproteases ADAMTS1 and ADAMTS5, are extensively co-expressed during mouse cardiac development. The mouse mutants of each gene have mild cardiac anomalies, however, their combined genetic inactivation to elicit cooperative roles is precluded by tight gene linkage. Therefore, we coupled Adamts1 inactivation with pharmacologic ADAMTS5 blockade to uncover stage-specific cooperative roles and investigated their potential substrates in mouse cardiac development. ADAMTS5 blockade was achieved in Adamts1 null mouse embryos using an activity-blocking monoclonal antibody during distinct developmental windows spanning myocardial compaction or cardiac septation and outflow tract rotation. Synchrotron imaging, RNA in situ hybridization, immunofluorescence microscopy and electron microscopy were used to determine the impact on cardiac development and compared to Gpc6 and ADAMTS-cleavage resistant versican mutants. Mass spectrometry-based N-terminomics was used to seek relevant substrates. Combined inactivation of ADAMTS1 and ADAMTS5 prior to 12.5 days of gestation led to dramatic accumulation of versican-rich cardiac jelly and inhibited formation of compact and trabecular myocardium, which was also observed in mice with ADAMTS cleavage-resistant versican. Combined inactivation after 12.5 days impaired outflow tract development and ventricular septal closure, generating a tetralogy of Fallot-like defect. N-terminomics of combined ADAMTS knockout and control hearts identified a cleaved glypican-6 peptide only in the controls. ADAMTS1 and ADAMTS5 expression in cells was associated with specific glypican-6 cleavages. Paradoxically, combined ADAMTS1 and ADAMTS5 inactivation reduced cardiac glypican-6 and outflow tract Gpc6 transcription. Notably, Gpc6−/− hearts demonstrated similar rotational defects as combined ADAMTS inactivated hearts and both had reduced hedgehog signaling. Thus, versican proteolysis in cardiac jelly at the canonical Glu441-Ala442 site is cooperatively mediated by ADAMTS1 and ADAMTS5 and required for proper ventricular cardiomyogenesis, whereas, reduced glypican-6 after combined ADAMTS inactivation impairs hedgehog signaling, leading to outflow tract malrotation.